Understanding Cryptocurrencies : Bitcoin, Ethereum, and Altcoins As an Asset Class. - Santos-Alborna, Ariel (New York : Business Expert Press, 2021)
Understanding Cryptocurrencies is perfect for both introductory investors to the digital asset space and experienced investors seeking to gain practical insight into frameworks for understanding digital assets and valuation metrics. The book provides in-depth analysis of Bitcoin, Ethereum, and the different types of Altcoins in the ecosystem. The author demonstrates an empirical approach to explaining how digital assets can fit into a diversified portfolio of traditional financial assets, or as a standalone portfolio in a parallel financial ecosystem.
Cover -- Halftitle -- Title -- Copyright -- Description -- Contents -- Introduction -- Chapter 1: What Is Bitcoin? -- Chapter 2: How Bitcoin Fits in Your Portfolio -- Chapter 3: Macroeconomics, Monetary Policy, and Bitcoin's Perfect Storm -- Chapter 4: Valuing Bitcoin -- Chapter 5: How to Invest in Bitcoin -- Chapter 6: A Look at Common Counterarguments -- Chapter 7: On Ethereum and Altcoins -- Chapter 8: Digital Assets in Your Portfolio -- Conclusion -- Notes -- References -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Cryptocurrencies; Bitcoin; Electronic funds transfers; Electronic books